Effect of grain processing at different barley varieties on nutrient compositions, starch contents and in vitro digestion parameters - Güney, Mehtap (Progress in Nutrition, 2019)
This study examined how response of treating with heat of twelve different barley varieties on nutrient composition, starch contents, in vitro dry matter digestibility (IVDMD) and in vitro organic matter digestibility (IVOMD). In the study, a total of twelve different barley varieties (Tarm-92, Avcı-2000, Çetin-2002, Özdemir, İnce, Bolayır, Anka-04, Tosunpaşa, Larende, Martı) were used. Processing with heat to all barley varieties were significantly higher contents of DM, OM and neutral detergent fiber (NDF). However, starch contents were significantly lower compared to unprocessing group (p<0.05). Treating with heat in term of IVDMD and IVOMD had importantly decreased in some varieties, while no change did in some varieties (p<0.05). Of all results, it was thought that treating with heat of barley varieties were important in term of regulating synchronization of energy and protein in rumen of nutrient digestion in ruminant as it increase the cell wall.